Analisis Hubungan Kecanduan Media Sosial Dengan Kecemasan Sosial dan Hubungan Interpersonal pada Remaja - Henisaputri, R Widya (Journal of Digital Ecosystem for Natural Sustainability, 2022)
This study aims to analyze the relationship between social media addiction on social anxiety and interpersonal relationships in adolescents. This study uses a quantitative approach with predictive correlation method. The instrument used in this study is a differential semantic scale for social media addiction, and a likert scale for social anxiety and interpersonal relationships. The research sample was 220 high school students in Batam City, Indonesia, who were selected by cluster quota random sampling. The results showed that social media addiction did not contribute to social anxiety with a t-value of -0.98, and social media addiction did not contribute to interpersonal relationships with a t-value of -1.05.